Geriatric hospital evaluation: a necessary tool - Ángel Julio Romero Cabrera; Leocadia Ernestina Amores Hernández; Yaknoy Cardona Alfonso (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Comprehensive Geriatric evaluation, understood as a tool of proven value by research, is realized in elderly patients. It is a process which allows understanding diverse medical and psycho-social conditions which influence their health. In addition to frequent diseases of the elderly population, social, psychological and environmental factors influence as well. In spite of its advantages, its usage in admitted patients is not widespread in all the services, so there are breaches between what is known and what is done. The present review, in a form of guideline, highlights conceptual aspects of hospital geriatric evaluation, its purposes, benefits, the process and the procedures to conduct it.